Design of Receiver Used for Passive Millimeter Wave Imaging System - Bao-hua Yang; Zhi-Ping Li; Tong-Fei Yu; Jin Zhang; Xian-Xun Yao; An-Yong Hu; Cheng Zheng; Jun-Gang Miao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As millimeter wave (MMW) electronic technologies have matured, the MMW imaging using for human security inspection is emerging as an effective approach to imaging through obscuring materials, such as clothing for concealed weapons detection or plastic mines. This paper introduces temperature sensitivity firstly and then the fringe-washing functions are derived which decide the structure the antenna array and the receivers of the system BHU-2D. Finally, the fringe-washing functions and their phases are calculated from the frequency responses of 24-receiver, they all show good consistency of the receivers which also can be proved from the test results of receivers. From the final imaging of our system, the 1-2K temperature sensitivity is realized successfully. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3012